Study of water quality in the distribution network of the centralized water supply system in the city of Lviv - Мацієвська, Оксана Олександрівна (Eastern-European Journal of Enterprise Technologies, 2015)
The problem of water quality change in the distribution network of the centralized water supply system in the city of Lviv is considered, and some results of our research in this area are presented. The main purpose of the research is identifying the main factors of water quality change in the distribution network of the city. During the research, collection, analysis and synthesis of data on technological parameters of the distribution network were carried out, and the data of the analysis of eight water samples taken from residents in different districts of the city of Lviv were used. The results suggest that the increase in total hardness and alkalinity of water is caused by mixing of water from different water intakes in the distribution network; water oxidability growth - by probable accidents with entry of organic pollutants into the pipeline; increase in the concentration of total iron - by corrosion of long-life and great-length sites of the distribution network; reduction of free residual chlorine - by its spending on oxidation of chemicals contained in water and elimination of pathogenic microorganisms of biofilms on the inner walls of pipes. In some water samples, an excess of requirements of physiological full value of the mineral composition of drinking water by total hardness and probable value of solids, due to their increased values in the source water was observed. However, the values of water quality indices in the studied sites do not exceed the norms applicable to drinking water. To prevent the deterioration of the drinking water quality, and, therefore, the health of residents, the introduction of modern systems of monitoring and modeling of water quality change in the distribution network is recommended.